Salt-bridge modulates differential calcium-mediated ligand binding to integrin α1- and α2-I domains - Brown, Kyle L. (Sci Rep, 2018)
Integrins are transmembrane cell-extracellular matrix adhesion receptors that impact many cellular functions. A subgroup of integrins contain an inserted (I) domain within the α–subunits (αI) that mediate ligand recognition where function is contingent on binding a divalent cation at the metal ion dependent adhesion site (MIDAS). Ca(2+) is reported to promote α1I but inhibit α2I ligand binding. We co-crystallized individual I-domains with MIDAS-bound Ca(2+) and report structures at 1.4 and 2.15 Å resolution, respectively. Both structures are in the “closed” ligand binding conformation where Ca(2+) induces minimal global structural changes. Comparisons with Mg(2+)-bound structures reveal Mg(2+) and Ca(2+) bind α1I in a manner sufficient to promote ligand binding. In contrast, Ca(2+) is displaced in the α2I domain MIDAS by 1.4 Å relative to Mg(2+) and unable to directly coordinate all MIDAS residues. We identified an E152-R192 salt bridge hypothesized to limit the flexibility of the α2I MIDAS, thus, reducing Ca(2+) binding. A α2I E152A construct resulted in a 10,000-fold increase in Mg(2+) and Ca(2+) binding affinity while increasing binding to collagen ligands 20%. These data indicate the E152-R192 salt bridge is a key distinction in the molecular mechanism of differential ion binding of these two I domains.